2020
DOI: 10.3390/app11010192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ECG Features for the Classification of Post-Stroke Survivors with a Diagnostic Approach

Abstract: Stroke is considered as a major cause of death and neurological disorders commonly associated with elderly people. Electrocardiogram (ECG) signals are used as a powerful tool in diagnosing stroke, and the analysis of ECG signals has become the focus of stroke research. ECG changes and autonomic dysfunction are reportedly seen in patients with stroke. This study aimed to analyze the ECG features and develop a classification model with highly ranked ECG features as input variables based on machine-learning techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Previous research has established that diagnostic easiness is a fundamental attribute for occupied non-specialist clinicians [ 53 ]. Studies in radiology [ 54 ], ophthalmology [ 55 ], and cardiology [ 56 ] have shown that ML methods may contribute to improving the medical service by AI-assisted workflow. The present study confirms and extends these findings to respiratory physiology showing that machine learning algorithms help diagnose respiratory abnormalities in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has established that diagnostic easiness is a fundamental attribute for occupied non-specialist clinicians [ 53 ]. Studies in radiology [ 54 ], ophthalmology [ 55 ], and cardiology [ 56 ] have shown that ML methods may contribute to improving the medical service by AI-assisted workflow. The present study confirms and extends these findings to respiratory physiology showing that machine learning algorithms help diagnose respiratory abnormalities in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, wearable sensors allow patients to execute their exercises at home relieving them of the drain of transportation. Subsequently, several types of sensing devices are used in applications extending from monitoring subjects' physiologic responses like Electromyography (EMG) [30], Electrocardiogram (ECG) [31], or glucose level in the blood [32] to evaluating kinematics of the individuals: gait, ROM, balance using Inertial Measurement Units (IMU) [33]. These sensors are employed in conjunction with clinical tests and outcome measures, such as sit-to-stand [34], Timed Up and Go (TUG) [35] to give an objective assessment and monitoring of the patient condition [36].…”
Section: Introductionmentioning
confidence: 99%